960 EARLY ONSET OF SUBTLE LIVER DAMAGE IN TTR AMYLOIDOSIS PATIENTS TREATED WITH TAFAMIDIS. (15th December 2022) - Agbariah, Andrea; Nannelli, Chiara; Comunello, Andrea; Cemin, Roberto
Abstract: Background: misfolded transthyretin amyloid fibrils can deposit in the myocardium causing transthyretin amyloid cardiomyopathy (ATTR-CM). Tafamidis has become recently available for the treatment of ATTR-CM, but to date very few data about its possible side effects have been published. Aims: to investigate the potential liver toxicity of Tafamidis 61 mg/day in a group of patients affected by wild type ATTR-CM treated in our department. Materials and Methods: 14 consecutive patients with wild-type ATTR-CM were treated with Tafamidis accordingly to the classical recommendations. The patients' liver function was checked through transaminases and gammaGT determination at baseline and for the first six months and their changes analysed with the non-parametric Wilcoxon test for paired samples. Results: mean age of the patients included (13 males and a female) was 78 years. Baseline transaminases were all within the normal range (median GOT level 25.0 U/L - IQR 19.0-29.0; median GPT levels 24.0 U/L - IQR 15.0-27.0) and remained stable for the first two months (median GOT at 2 months 25.5 U/L - IQR 19.0-28.0; median GPT at 2 months 22.5 U/L – IQR 16.0-27.0). Median GGT baseline level was 138.0 U/L (IQR 58.0-204.0) and raised to 142.0 U/L (IQR 56.0-270.0) after a two-month therapy (p<0.01). The further follow-up confirmed a similar trend in the first six month of treatment, with a linear and constant increase of gammaGT levels. Conclusions: even not clinically relevant, the wild-type ATTR-CM patients included in our analysis showed all a subtle increase of gammaGT values after only two months of Tafamidis treatment, which was confirmed at six months. This observation underlines the potential hepatotoxicity of the drug, thus confirming the recommendations of strict and regular liver function analysis provided by the manufacturer.